Use of untreated wastewater in peri-urban agriculture in Pakistan: risks and opportunities - Ensink, Jeroen H.J.; Hoek, Wim van der; Matsuno, Y.; Munir, S.; Aslam, M.R. (International Water Management Institute, 2002)
The practice of using untreated wastewater for irrigation is widespread but has been largely ignored because the norm has always been that wastewater should be treated before use. Increasing water scarcity, lack of money for treatment and a clear willingness by farmers to use untreated wastewater have led to an uncontrolled expansion of wastewater use. It is therefore important to better document the practice of irrigation with untreated wastewater in order to find out how it can be improved within the financial possibilities of very low-income countries.